Bark, Spike, bark! - David, Luke.; Ulrich, George (New York : Simon Spotlight, 1998)
Chuckie and Tommy misconstrue Stu's efforts at car repair with "bark plugs" as an attempt to silence the family dog.
"Based on the TV series Rugrats created by Klasky/Csupo Inc. and Paul Germain as seen on Nickelodeon"--P. [4] of cover.
Keywords: Babies -- Fiction; Dogs -- Fiction; Automobiles -- Maintenance and repair -- Fiction